2017
DOI: 10.1002/humu.23175
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Functional, and Clinical Characterization of a NovelPTPN11Mutation Cluster Underlying Noonan Syndrome

Abstract: Germline mutations in PTPN11, the gene encoding the Src-homology 2 (SH2) domain-containing protein tyrosine phosphatase (SHP2), cause Noonan syndrome (NS), a relatively common, clinically variable, multisystem disorder. Here, we report on the identification of five different PTPN11 missense changes affecting residues Leu , Leu , and Arg in 16 unrelated individuals with clinical diagnosis of NS or with features suggestive for this disorder, specifying a novel disease-causing mutation cluster. Expression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 45 publications
10
28
0
3
Order By: Relevance
“…Our results confirm the relatively low frequency of significant dermatological manifestations in PTPN11 ‐NS, excluding PTPN11 ‐NSML, with the exception of easy bruising present in more than half the patients and are broadly comparable with previous findings of frequencies varying from 30% to 65% . Wavy or curly hair and temporal alopecia/scarce scalp hair were present in 23% and 15% of cases, respectively; this was similar to the previously reported frequency varying from 15% to 29% and 11% to 17%, respectively . Considering their relatively lower frequencies and the potentially significant changes in scalp hair characteristics during childhood and adolescence in NS, these hair abnormalities appear to be of little use for diagnosing NS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results confirm the relatively low frequency of significant dermatological manifestations in PTPN11 ‐NS, excluding PTPN11 ‐NSML, with the exception of easy bruising present in more than half the patients and are broadly comparable with previous findings of frequencies varying from 30% to 65% . Wavy or curly hair and temporal alopecia/scarce scalp hair were present in 23% and 15% of cases, respectively; this was similar to the previously reported frequency varying from 15% to 29% and 11% to 17%, respectively . Considering their relatively lower frequencies and the potentially significant changes in scalp hair characteristics during childhood and adolescence in NS, these hair abnormalities appear to be of little use for diagnosing NS.…”
Section: Discussionsupporting
confidence: 91%
“…Considering their relatively lower frequencies and the potentially significant changes in scalp hair characteristics during childhood and adolescence in NS, these hair abnormalities appear to be of little use for diagnosing NS. We observed KP in 18·5% of patients, which is a relatively higher frequency than 6% as previously reported, but not significant given that KP frequencies in children and adolescents in the general population vary from 2% to 26% …”
Section: Discussionsupporting
confidence: 47%
“…At most one pathogenic allele at a given codon was observed in any population cohort with a minimum of 1000 individuals, 15, 17, 19 thus validating these MAF thresholds while recognizing that an occasional individual could be undiagnosed in the general population. Furthermore, a variant, PTPN11 p.Arg265Gln, presenting in patients with likely unrecognized mild phenotypic features 20 also fell below these conservative thresholds. These assessments concluded that a variant should be completely absent from large population cohorts for PM2 usage.…”
Section: Resultsmentioning
confidence: 94%
“…Nonsense mutations are among the most common types of disease‐associated mutation involving NF1 , with mutations occurring around codon 1152 known to be pathogenic (Ars et al , ). Case 1 also harboured a PTPN11 mutation, which disrupts its autoinhibitory domain, leading to increased MAPK signaling (Pannone et al , ). This precise variant has been identified in the germline of patients with Noonan Syndrome.…”
Section: Discussionmentioning
confidence: 99%